National Mafia-Type Organisations: Local Threat, Global Reach (2016)
A first challenge in characterising and quantifying the nature and dimension of the extortion rackets phenomenon worldwide is that extortion is an umbrella concept grouping a large array of criminal practices. Extortion is often associated with long-standing and well-organised criminal organisations, such as the Italian Mafia and the Japanese Yakuza, given the amount of data and research about these criminal groups and their popularity in contemporary popular culture. Yet, a review of the different extortion practices around the world quickly makes readily available the significant diversity and complexity of the social contexts in which extortion occurs. This chapter provides a brief review of typical dynamics of extortion in different countries around the world. The main goal is, first, to summarily show the persistence and diversity of extortion rackets worldwide and, second, and most important, to contextualise the two cases analysed in the following chapters, by providing some points of contrast, regarding the social conditions of the phenomenon of extortion, as well as their academic accessibility.